Activation of c-Jun/JNK signaling predicts poor prognosis in nasopharyngeal carcinoma - Zhang, Yu-Jie (Int J Clin Exp Pathol, 2018)
A significant proportion of patients with nasopharyngeal carcinoma (NPC) will develop regional relapse or distant metastasis after treatment. This present study evaluated the role of c-Jun/JNK signaling pathways in NPC and its relationship with prognosis. Our study enrolled 122 patients diagnosed with NPC and 136 chronic nasosinusitis patients. Immunohistochemistry was applied to detect positive expression of c-Jun, JNK, p-c-Jun, and p-JNK proteins. Receiver operating characteristic (ROC) curve was then adopted to assess the diagnostic value of c-Jun/JNK signaling pathways for NPC. Activated c-Jun/JNK signaling pathways were observed in NPC patients. Activation of c-Jun/JNK signaling was associated with TNM staging of NPC, as NPC patients with stage III-IV had higher positive expression rates of c-Jun, JNK, p-c-Jun, and p-JNK proteins compared to NPC patients with stage I-II. According to ROC curve results, areas under the curve of c-Jun, JNK, p-c-Jun, and p-JNK protein expression were 0.943, 0.968, 0.963, and 0.938, respectively. The 1-, 3-, and 5-year survival rates and mean survival times of dead patients were lower and shorter in patients with positive expressions of c-Jun, JNK, p-c-Jun, and p-JNK than those with negative expression (all P < 0.05). Overexpression of c-Jun/JNK is associated with development and progression of NPC, indicating that c-Jun/JNK serves as a predictive indicator for early diagnosis and prognosis of NPC.